A Highly Stable and Insensitive Fused Triazolo–Triazine Explosive (TTX). Issue 8 (21st December 2016) - Kumar, Dheeraj; Imler, Gregory H.; Parrish, Damon A.; Shreeve, Jean'ne M.
Abstract: A fused‐ring conjugated energetic molecule, 4‐amino‐3, 7‐dinitro‐[1, 2, 4]triazolo[5, 1‐c] [1, 2, 4]triazine (TTX), has been synthesized in good yield in a two‐step process starting from the known 5‐amino‐3‐nitro‐1 H ‐1, 2, 4‐triazole (ANTA). Characterization of TTX shows that it possesses energetic properties approaching those of 1, 3, 5‐trinitro‐1, 3, 5‐triazacyclohexane (RDX), but with a higher thermal stability and lower sensitivity towards impact and friction. Abstract : TTX, a sleeping giant : A highly stable and insensitive fused‐ring triazole– triazine explosive, (TTX), with energetic properties approaching those of RDX, was synthesized and fully characterized.